Iron Discipline and Personnel Policy in The Army of Amir Temur - Eshmurodov Bakhodir Tursunkulovich (American Journal Of Social Sciences And Humanity Research, 2025)
This article discusses the military discipline and personnel policy of the great commander Amir Temur, who left a distinct mark on world history, which played an important role in forming the most powerful army of his time and building a large centralized state. Meanwhile, from a historiographical point of view, scientific literature written by Uzbek historians during the years of independence on this topic has been studied, supplemented by sources and information from foreign researchers, and problematic aspects have been explained. The article also pays special attention to aspects related to the mobilization system in the Sahibkiran army. Scientific research by Uzbek historians and orientalists emphasizes that the army of Amir Temur was dominated by the ideas of mutual respect between commanders and subordinates, the rule of law and tolerance in military units. According to scientific research that analyzed the information from the first sources, Sahibkiran managed to implement almost flawlessly the important components of military management, such as the staffing of military units and the selection of fighters, as well as the establishment of strict discipline in the army. It should be noted that the article uses such well-known sources as the “Tuzuki Temuriy” (Temur's Statutes), “Zafarname” by Persian historians Ali Yazdi and Nizomiddin Shami, “Ajayib al-Makdur fi tarihi Taymur” by the Arab historian Ibn Arabshah, which cover in detail the history of the period of Sahibkiran and the Timurids, as well as research by modern Uzbek and Russian orientalists.